2006
DOI: 10.1002/humu.20285
|View full text |Cite
|
Sign up to set email alerts
|

Mutations of the TGF-β type II receptorBMPR2 in pulmonary arterial hypertension

Abstract: Communicated by Maria Rita Passos-BuenoPulmonary arterial hypertension (PAH) is clinically characterized by a sustained elevation in mean pulmonary artery pressure leading to significant morbidity and mortality. The disorder is typically sporadic, and in such cases the term idiopathic PAH (IPAH) is used. However, cases that occur within families (familial PAH (FPAH)) display similar clinical and histopathological features, suggesting a common etiology. Heterozygous mutations of a type II member of the TGF-b ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
295
2
10

Year Published

2008
2008
2012
2012

Publication Types

Select...
7
3

Relationship

3
7

Authors

Journals

citations
Cited by 378 publications
(318 citation statements)
references
References 50 publications
(68 reference statements)
7
295
2
10
Order By: Relevance
“…More than 140 distinct mutations of BMPR2 gene have been identified in patients with PAH from a wide range of ethnic groups. 8 In this study, we identified three novel exonic mutations of the BMPR2 gene in the Chinese PAH patients (Table 2), including a frame shift mutation in exon 5 (Leu203fsX15), a nonsense mutation in exon 3 (Glu98X) and a missense mutation in exon 12 (Ser863Asn). These disease-causing mutations are predicted to affect different domains of the BMPR2 protein and mutations within different regions may vary in their impact on disease initiation and progression.…”
Section: Discussionmentioning
confidence: 91%
“…More than 140 distinct mutations of BMPR2 gene have been identified in patients with PAH from a wide range of ethnic groups. 8 In this study, we identified three novel exonic mutations of the BMPR2 gene in the Chinese PAH patients (Table 2), including a frame shift mutation in exon 5 (Leu203fsX15), a nonsense mutation in exon 3 (Glu98X) and a missense mutation in exon 12 (Ser863Asn). These disease-causing mutations are predicted to affect different domains of the BMPR2 protein and mutations within different regions may vary in their impact on disease initiation and progression.…”
Section: Discussionmentioning
confidence: 91%
“…Heritable forms of PAH include clinically sporadic idiopathic PAH (IPAH) with germline mutations (mainly of the bone morphogenetic protein receptor 2 gene as well as the activin receptor-like kinase type-1 gene or the endoglin gene) and clinical familial cases with or without identified germline mutations [14,15]. This new category of heritable PAH does not mandate genetic testing in any patient with IPAH or in familial cases of PAH because this would not change the clinical management.…”
Section: Clinical Classification Of Pulmonary Hypertensionmentioning
confidence: 99%
“…Heterozygous germ line mutations in the BMP receptor II gene (BMPRII) have been found in more than 80% of familial PAH patients. In addition, about 20% of patients with idiopathic PAH were reported to have mutations in BMPRII [99,100]. A recent study has implicated mutations of ALK1 in children with PAH [101].…”
Section: Pulmonary Arterial Hypertensionmentioning
confidence: 99%